Distinct Characteristics of Small Cell Lung Cancer Correlate With Central or Peripheral Origin: Subtyping Based on Location and Expression of Transcription Factor TTF-1. Issue 51 (December 2015) - Miyauchi, Eisaku; Motoi, Noriko; Ono, Hiroshi; Ninomiya, Hironori; Ohyanagi, Fumiyoshi; Nishio, Makoto; Okumura, Sakae; Ichinose, Masakazu; Ishikawa, Yuichi
Abstract : Abstract: Small-cell lung carcinoma (SCLC) is a type of lung cancer with neuroendocrine differentiation and a poor prognosis that is widely believed to arise in the central lung. Thyroid transcription factor-1 (TTF-1) is a peripheral marker of lung adenocarcinoma that is also highly expressed in SCLC. In this study, we examined whether SCLC is really a central-type tumor and the relationship between tumor location, TTF-1 expression and prognosis of SCLC. Ninety six SCLCs, diagnosed from biopsies or surgical materials, for which detailed computed tomography (CT) images were available, were collected consecutively from Japanese patients between 2004 and 2011. We examined the location of the primary tumor (central or peripheral) using thin-sliced CT, a TTF-1 immunohistochemical expression, and clinicopathology including prognosis. Of the 96 SCLCs, 74% (71/96) were of the peripheral type and found to have a significantly worse prognosis than central-type tumors. TTF-1 immunoreactivity was identified in 79 tumors (82%), 78% of which (62/79) were of the peripheral type and 22% of which were central. TTF-1 expression was significantly correlated with peripheral location ( P  = 0.030). Multivariate analysis revealed that high TNM stages and the peripheral location were independent markers for poor survival. The majority of SCLCs were of the peripheral type. The peripheral-type SCLC expressed TTF-1 more frequently and had a poorer prognosis than central-type tumors did. Further analysis on original sites of SCLC, using molecular methodology, or based on another ethnicity, should be warranted. Abstract : Supplemental Digital Content is available in the text